Estrategias didácticas para fortalecer la Educación Ambiental en los estudiantes, 9° grado “A” de la Unidad Educativa “Lauro Damerval Ayora”, período 2023 - Morocho Pardo, Jenny Selena (2024)
This research aims to identify effective didactic strategies for enhancing Environmental Education among 9th-grade students in Class 'A' of Basic General Education (BGE) at the 'Lauro Damerval Ayora' educational unit during the 2023 academic period. The study employs a qualitative- quantitative approach with a descriptive design, utilizing a non-experimental methodology. The theoretical framework encompasses topics related to Didactic Strategies and Environmental Education. Scientific, descriptive, analytical, synthetic, and statistical methods were employed throughout the investigative process. Information was collected through a student survey and a structured interview with the teacher. The research population includes twenty-nine students and one teacher from the ninth grade, parallel 'A' at the “Lauro Damerval Ayora” educational unit. The results suggest the presence of didactic strategies aimed at reinforcing environmental education within the institution. However, these strategies appear to lack the necessary commitment and empowerment to sustain environmental education among both students and the broader educational community. To address this issue, a didactic booklet titled "Guardians to Environmental Rescue" was planned and successfully implemented. The booklet incorporated didactic strategies that contributed to enhancing knowledge about Environmental Education topics. It was used in a didactic and innovative manner, involving students in practical activities and direct experiences with the environment. The booklet proved to be an effective tool in strengthening commitment and awareness of environmental care within the educational unit.